Cardiovascular repercussions resulting from the Multisystem Inflammatory Syndrome after COVID-19 infection in pediatric age: an integrative review (Research, Society and Development, 2022)
The pediatric population constitutes only 2% of COVID-19 cases, however, cases of inflammatory shock, ventricular dysfunction and thrombotic events have been reported. This set of signs is called Multisystem Inflammatory Syndrome (MIS-C), also characterized by hyperpyrexia and generalized organ failure, with a direct relationship with SARS-COV-2 infection. The present work aims to synthesize the evidence of cardiovascular manifestations resulting from the Post COVID-19 Multisystem Inflammatory Syndrome in pediatric age (PMIS-TS). For this Integrative Review, carried out through the PubMed and Science Direct platforms between 2020 and 2022, the descriptors elected were ''Inflammation'', ''Pediatrics'', ''Covid-19'' and ''Cardiology'', associated to the Boolean operator ''AND''. Inclusion criteria consisted of (1) clinical trials, controlled and randomized trials, reviews and meta-analyses; (2) studies on the cardiovascular repercussions of PMIS-TS; (3) studies on pediatric cardiomyopathies resulting from coronavirus infection; (4) articles on management and treatment of PMIS-TS. Exclusion criteria included inadequacies to the topic, assessments of other clinical conditions, in addition to non-specific texts when addressing MIS-C. It was observed that the cases of PMIS-TS had echocardiograms and magnetic resonance imaging predictive of myocarditis, valvulitis and coronary heart disease, findings corroborated by laboratory alterations. The electrocardiograms included premature beats and various arrhythmias. In the analysis of the 54 articles, it was identified that, despite the pediatric age group corresponding to the smallest share of COVID-19 cases, children are susceptible to potentially serious repercussions. Thus, the hyper-inflammatory state can lead to death, and it is essential to conduct new studies with assertive therapeutic options for the aforementioned conditions.